A morte na territorialidade digital : espetáculo, consumo e gestão do medo nas redes sociais - Sangalli, Heryck Luiz Jacob (2017)
The present research is aimed to investigate approaches concerning death on the digital social network Facebook. The hypotheses to analyze the theme consider that death is related to spectacle, consumption and management of fear. The production of content regarded to this perspective is only made possible by means of the current media-based society in which digital social networks prospered because it provided tools for the development of locus. Thus, our empirical object of analysis is Jogos Mortais +18 and Faca na Caveira, two Brazilian pages in which contents referring to the death are posted. The study is divided into three parts that build the theoretical framework by means of a bibliographical review: death, media-based society and social networks on the Internet as a source of new territorialities; and spectacle, consumption and fear, as mentioned above. Next, ethnographic observation and content analysis as a methodology are applied. In order to understand how death is experienced in the wide day-to-day of Facebook, a survey aimed at users was conducted. In this manner, it is concluded that death is actually connected to spectacle, information consumption, and management of fear, appropriated by specific individuals to manage control. In addition, we have confirmed that death is part of Facebook's daily living and sociability, and also consumed by users who are not included in pages that publish such subject